Concentrating or Sprinkling? Federal Funding for Indigenous, Women's, and Environmental NGOs in Canada, 1972-2014. (November 2017) - Corrigall-Brown, Catherine; Ho, Mabel
Governments have a long history of funding nongovernmental organizations (NGOs) and their programs. While there is much work describing this funding, there has been little research systematically examining how the political and economic context shapes the level and type of funding NGOs receive. This article examines the factors that predict levels of government funding for NGOs over time, focusing on spending for interest groups in three areas, Indigenous, women, and the environment. We use data collected from the Canadian Public Accounts, which lists all grants to groups by the federal government from 1972 until 2014. We use these data to assess how federal funding has changed over this period, how funding across issue areas is related, and the role of political and economic factors in shaping rising and declining funding over time. We find that the factors that predict funding vary across issue areas. Our analysis also shows government's tendency to sprinkle funding across a larger number of groups or concentrate it in a smaller number of organizations is strongly related to the party in power and the issue area.